Supply Chain Resilience: Conceptualization of Total Quality Management and Performance of Kenya Medical Supplies Authority - Wahome John Ndungu; Stephen Makau Muathe (European Scientific Journal, ESJ, 2025)
Total Quality Management is an essential management approach that enables organizations and leaders in the modern era to leverage strategic management in running successful businesses. Managers are empowered to improve the quality of services and products by incorporating key total quality management principles, including fact-based decisions, process-centric approaches, relationship management, and employee engagement. However, the Kenya Medical Supplies Authority has faced scrutiny due to inefficiencies and service delivery delays, which are hindering access to essential healthcare services. This study focuses on assessing the Kenya Medical Supplies Authority's performance in applying the four Total Quality Management principles, which received inadequate attention in previously reviewed research. The study is grounded in four theoretical foundations: resource-based view, dynamic capabilities, stakeholder theories, and Deming’s theory of quality management. A descriptive research design was incorporated to guide data collection, targeting employees at the Authority with its headquarters in Nairobi County. A total of 181 respondents were sampled from a population of 330 employees. Sampling techniques for this study involved proportionate stratified and simple random sampling to guarantee representative participation from different management levels, including top, middle, and operational staff. Primary data was gathered using structured questionnaires, and a pilot test comprising 18 respondents from the Mission for Essential Drug Supplies was performed to evaluate the validity and reliability of the instrument. The data were analyzed quantitatively using both descriptive and inferential statistics with SPSS version 25. The findings on regression analysis indicate a strong relationship between these variables and performance (R = 0.765, R² = 0.585, F (4, 135) = 55.036, p < 0.001), pointing out that TQM practices explain 58.5% of the variance in organizational performance. Fact-based decisions had the highest impact (B = 0.372, t = 5.239, p < 0.001), followed by employee engagement (B = 0.348, t = 4.640, p < 0.001), process-centric approach (B = 0.319, t = 4.691, p < 0.001), and relationship management (B = 0.257, t = 3.134, p = 0.002). The findings point to the importance of continuous staff training, participatory leadership, and integrated data systems to enhance performance. The study recommends targeted mentorship for junior staff, regular evaluations to improve decision-making, and fostering a supportive organizational culture to sustain quality improvements.